Penyengat Island Riau Island: Towards A World Heritage - Anastasia Wiwik SWASTIWI (Indonesia Strategic Sustainability, 2022)
Malay history and culture cannot be separated from the existence of Penyengat Island. This island once had a strategic role. First, Penyengat Island was the fortress of Raja Haji during the war against the Dutch. Second, as the administrative center of the Riau-Lingga Kingdom. Third, to become the center of Islamic Malay studies which is well-known in the Malay world. Various disciplines have existed on this island. Studies from various disciplines have been carried out. The results mostly recommend that Penyengat Island provide lessons for the life of the Malay community now and in the future. This study uses the historical method through four stages of work, namely heuristics (collection of sources), source criticism (external to the material and internal to the content), interpretation and historiography. The primary sources are Malay manuscripts that were born on Penyengat Island in the late 19th and early 20th centuries. The secondary sources are scientific journals and government policies that discuss Penyengat Island. These primary and secondary sources are then analyzed and interpreted. The final stage is historiography to strengthen the narrative and support data for the submission of Penyengat Island as a world heritage. Penyengat Island has a tangible and intangible cultural heritage. The forerunner of the Indonesian language is recognized as being born from there. Penyengat Island deserves to be a world heritage.